Histograms of the Caspian Sea Hydrometeorological Parameters - Kostianoy Andrey; Lebedev Sergey; Bocharov Aleksandr A.; Kosolapov Il'ya A.; Tretiyak Il'ya; Volkov Daniil S.; Kravchenko P. N. (Russian Journal of Earth Sciences, 2023)
The article analyzes histograms of the distribution of the main hydrometeorological parameters of the Caspian Sea for 1980–2021 – air temperature, atmospheric pressure, absolute humidity, atmospheric precipitation and wind speed according to the MERRA-2 atmospheric reanalysis. Histograms were constructed for the entire study region of the Caspian Sea (36◦–48◦N, 45.625◦–55◦E), as well as separately for land and sea areas. The extremeness criteria were calculated based on the normal distribution and the real histogram for all 5 main meteorological parameters. A comparison was made of histograms obtained from MERRA-2 data and from weather station at Derbent located on the coast of the Caspian Sea. Distributions of average monthly wind speed, integral water vapor content and water vapor content in clouds over the Caspian Sea were also constructed according to microwave radiometry (SMMR, SSM/I) data for the time interval 1980–2021.